Analysis and Design of Web-based Internal Office Memo (IOM) Management System - Veza, Okta; Larisang, Larisang; Setyabudhi, Albertus Laurensius; Arifin, Nofri Yudi; Syofiawan, Doni; Martino, Hisar Gusdian (AI Society & STMIK Indonesia, 2024)
This research focuses on the design and implementation of a web-based Internal Office Memo (IOM) Management System in the PT InnoArk Servis Internasional Optipedia Team. The main problem relates to ineffective communication and coordination between divisions, which results in backlogs and repetition of work as well as difficulties in monitoring task progress. The research method adopts a System Development Life Cycle (SDLC) approach with a waterfall model and uses the Unified Modeling Language (UML) for system design. Implementation was carried out by utilizing the CodeIgniter framework and MySQL as a database, followed by black box testing of the requirements testing type. The result is a system that successfully improves operational efficiency, team collaboration, and transparency of work progress. This application not only overcomes communication obstacles, but also provides a basis for making better decisions based on actual data, maintaining the smooth implementation of tasks, and improving the quality of team collaboration in the PT InnoArk Servis Internasional Optipedia Team.